2015
DOI: 10.5489/cuaj.2749
|View full text |Cite
|
Sign up to set email alerts
|

Minimal fat renal angiomyolipoma with lymph node involvement: A case report and literature review

Abstract: E568Cite as: Can Urol Assoc J 2015;9(7-8):E568-71. http://dx.doi.org/10.5489/cuaj.2749 Published online August 10, 2015. AbstractRenal angiomyolipomas (AML), consisting of fatty tissue, blood vessels, and smooth muscular cells in various proportions, is a relatively common benign renal neoplasm. Simultaneous involvement of the kidney and lymph nodes is uncommon and might be confused with an advanced renal cancer. AML is divided into minimal fat AML and fat-predominant AML. However, minimal fat AML with lymph n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We searched English-language articles in the Medline database using the key words “kidney” or “renal,” “angiomyolipoma” or “hamartoma” and “lymph node.” Twenty-two papers were found. Based on the full text of the articles rather than only the abstracts, 16 papers and 25 cases were found to be relevant 4 19 ( Table 1 ). Busch et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We searched English-language articles in the Medline database using the key words “kidney” or “renal,” “angiomyolipoma” or “hamartoma” and “lymph node.” Twenty-two papers were found. Based on the full text of the articles rather than only the abstracts, 16 papers and 25 cases were found to be relevant 4 19 ( Table 1 ). Busch et al.…”
Section: Discussionmentioning
confidence: 99%
“…Twentytwo papers were found. Based on the full text of the articles rather than only the abstracts, 16 papers and 25 cases were found to be relevant [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (Table 1). Busch et al 4 reported the first two cases of benign renal AML with regional lymph node involvement in 1976.…”
Section: Discussionmentioning
confidence: 99%